2019
DOI: 10.1186/s12884-019-2329-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gestational diabetes mellitus in systemic lupus erythematosus pregnancy: a systematic review and meta-analysis

Abstract: Background It is well established that the risks of insulin resistance and diabetes mellitus are elevated in systemic lupus erythematosus (SLE) patients. However, the relationship between SLE pregnancy and gestational diabetes mellitus (GDM) is still obscure. We perform the present systematic review and meta-analysis to determine the relationship between GDM and SLE pregnancy. Methods According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
14
1
1
Order By: Relevance
“…Thirteen (27.1%) patients presented with lupus nephritis (LN). This diagnosis of LN was made primarily before pregnancy (10, 76.9%) and confirmed by biopsy in ten (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This last association was statistically significant (p < 0.0071) (Table 3).…”
Section: Characterization Of Lupus Nephritis Patientsmentioning
confidence: 79%
See 1 more Smart Citation
“…Thirteen (27.1%) patients presented with lupus nephritis (LN). This diagnosis of LN was made primarily before pregnancy (10, 76.9%) and confirmed by biopsy in ten (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This last association was statistically significant (p < 0.0071) (Table 3).…”
Section: Characterization Of Lupus Nephritis Patientsmentioning
confidence: 79%
“…16 Our current results on maternal complications during pregnancy are fully supported by other recently published studies in which common complications, such as premature birth, preeclampsia, thromboembolic disease, fetal death, and gestational diabetes, are significantly higher in patients with SLE. 16,[19][20][21] Preterm labor and birth are of great interest to public health entities because of their significant contribution to perinatal morbidity. Preterm infants are at a greater risk for short and long-term adverse outcomes, higher risk of neonatal death within the first month of life, 22 and neurodevelopmental sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of gestational diabetes is also increased in SLE pregnancy [22,36]. It is mainly related to glucocorticoid therapy during pregnancy.…”
Section: Maternal and Fetal Complications During Lupus Pregnancymentioning
confidence: 99%
“…This may be due to the fact, that lupus develops in a younger age than diabetes mellitus 2 [14]. The relationship between SLE and gestational diabetes has been studied in a meta-analysis [83]. It was found that SLE does not seem to increase the risk of gestational diabetes.…”
Section: Diabetes Mellitusmentioning
confidence: 99%